Patient-centered outcomes with subcutaneous immunoglobulin use for infection control in primary and secondary immunodeficiencies: data of a GEIE Spanish Registry - Martínez Mercader, Sandra; Garcia-Bustos, Victor; Moral Moral, Pedro; Martínez Buenaventura, Carmen; Escudero Vergara, Elisa; Montaner Bosch, María Carmen; Balastegui-Martín, Héctor; Galindo Maycas, Sonia; Palací Mur, Berta; Escobar Palazón, Marian; Moreno Mulet, María; Campanero Carrasco, Ignacio; et al. (Frontiers in Immunology, 2025)
Background and aimSubcutaneous immunoglobulin (SCIg) has emerged as an alternative to intravenous administration for patients with primary (PID) and secondary immunodeficiencies (SID), offering benefits such as fewer systemic adverse reactions and greater patient autonomy. However, comprehensive real-world data on SCIg use, including clinical and patient-centered outcomes, remain scarce. This study, conducted by expert immunodeficiency nursing teams, assesses the clinical characteristics, reported adverse effects, and quality-of-life outcomes associated with SCIg therapy with different formulations in patients with PID and SID across Spain.MethodsA multicenter, cross-sectional study was conducted across 8 immunodeficiency nursing units in Spain, involving 223 adult patients treated with SCIg from 2004 to 2024. Data on demographics, comorbidities, SCIg treatment characteristics, reported adverse events, and quality-of-life metrics (EuroQol-5D-3L, Gijón Scale) were collected and analyzed.ResultsThe cohort (61.4% female, mean age: 47.1 years) included 65% PID patients, with common variable immunodeficiency being the most frequent diagnosis (39.8%). SCIg demonstrated good tolerability overall, with no significant differences in global adverse event rates between facilitated 10% (fSCIg) and 20% formulations. However, 10% fSCIg was associated with higher reported frequencies of mild local rash (58.7% vs. 36.9%, p=0.002) and fever (10.6% vs. 1.7%, p=0.01). Quality-of-life scores indicated minimal limitations in mobility and self-care, with a mean subjective health rating of 72.7/100. Patients using 20% SCIg required fewer educational sessions for self-administration compared to the 10% group.ConclusionThe different SCIg formulations in this large, multicenter cohort was effective and generally well-tolerated, supporting its use for maintaining adequate IgG levels and promoting patient independence in PID and SID. The study’s findings advocate for tailored approaches that optimize patient satisfaction and address individual needs, emphasizing the critical role of dedicated immunodeficiency nursing teams in ensuring safe, effective, and patient-centered SCIg administration.